Integrating GIS with f-AHP for locating a single facility - Önden, İsmail (Transport, 2018)
Location selection problems stand out as popular research topics. Due to the popularity, different solution approaches emerged in the literature. Multi-criteria Decision Making (MCDM) techniques are examples of the solution approaches and they are frequently used because of their ordering capability in ranking the decision alternatives and success in representing decision makers’ experiences. On the other hand, Geographic Information Systems (GIS) is able to perform different spatial data analysis and provide geographic material. To reach a better decision, integration of experts’ opinions and certain geographic information derived from GIS is necessary. Within this context, in this paper, integration of the GIS abilities with Fuzzy Analytic Hierarchy Process (F-AHP) is discussed with two different integration methodologies for locating single facility. A hypothetical case study is provided to determine a location problem, which focuses on logistics activities. The results have shown that both proposed methodologies are able to order location alternatives in multiple criteria environments.